2011
DOI: 10.1007/s10453-011-9235-x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobiological investigations inside repositories of the National Archive of the Republic of Cuba

Abstract: The objectives of this study were to evaluate the microbial prevalence inside six repositories of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 26 publications
3
13
0
12
Order By: Relevance
“…Alternaria has been previously detected by the viable (Arnold et al, 1987;Rojas et al, 2002) and nonviable methods (Herrera et al, 2003), but this is the first time, they are identified at species level in Caribbean outdoor areas. Alternaria tenuissima has been reported in other parts of the world (AbuDieyeh et al, 2010) and N. sphaerica has been mainly found in Cuban aerobiological indoor environments (Borrego & Perdomo, 2012).…”
Section: Airborne Fungus Spores In Havana 295mentioning
confidence: 99%
See 2 more Smart Citations
“…Alternaria has been previously detected by the viable (Arnold et al, 1987;Rojas et al, 2002) and nonviable methods (Herrera et al, 2003), but this is the first time, they are identified at species level in Caribbean outdoor areas. Alternaria tenuissima has been reported in other parts of the world (AbuDieyeh et al, 2010) and N. sphaerica has been mainly found in Cuban aerobiological indoor environments (Borrego & Perdomo, 2012).…”
Section: Airborne Fungus Spores In Havana 295mentioning
confidence: 99%
“…Syncephalastrum racemosum, Rhizopus stolonifer and R. oryzae have been previously reported in indoor environments of Cuba only, mainly in warehouses and stores (Borrego & Perdomo, 2012). Trichoderma was previously isolated from indoor and outdoor environments (Borrego et al, 2010).…”
Section: Airborne Fungus Spores In Havana 295mentioning
confidence: 99%
See 1 more Smart Citation
“…Estos plantean que dichos gé-neros son los géneros más representativos en el aire tanto de interiores como de exteriores, por lo que se consideran contaminantes por excelencia del patrimonio cultural. Otros autores [31][32][33][34][35][36][37] han demostrado que los conidios de Aspergillus y Penicillium en general son más numerosos en el aire de interiores que de exteriores de lo que se deduce que muchos de ellos provienen de los materiales y soportes contaminados en dicho medio. Penicillium es el género más abundante en ambientes interiores de viviendas y Aspergillus es el más común en el aire de viviendas húmedas al igual que en archivos, museos y almacenes soterrados seguido de Penicillium [33].…”
Section: Museo Biblioteca Servando Cabrera Morenounclassified
“…Such risks appears to be lower in naturally ventilated buildings in comparison to those ventilated through mechanical means. For instance, in an earlier study conducted by Borrego and Perdomo [5], fungal contamination was reported to be reduced in buoyancy driven ventilated building than the forced ventilated counterparts. The reason, according to the study, is not unconnected with the natural ventilation that facilitate movement of particles in the air thereby making spores deposition difficult.…”
Section: Introductionmentioning
confidence: 95%